FROM LIKES TO RIDES: HOW SOCIAL MEDIA MARKETING ACTIVITIES TRANSFORMS INTO PURCHASE DECISION IN BUS SERVICES - Roosdhani, Mohamad Rifqy; Komaryatin, Nurul; Arifin, Samsul; Ali, Ali; Huda, Nurul (JURNAL EKOBIS DEWANTARA, 2024)
It is now vital to companies to promote via social media in order to remain in operation. Almost all business sectors need to use social media to boost customer trust, brand equity, and market expansion. Social networking has a role in the operation of the transportation industry. There hasn't been much study about social media advertising in the transportation sector throughout the years, particularly when it comes to bus transportation. In an effort to improve purchase decisions via the use of SMMS, this study yielded a novel perspective. It was discovered that the perceived quality and participation factors are required as the mediation variables between SMMS and bought Decisions in order to get the best possible results to enhance buying decisions. Purposive sampling is used in the research to gather and check data from samples of 506 bus passengers at Bejeu Jepara PO in a quantitative manner. An empirical model was evaluated using Smart PLS 4.0 software after data were collected via a questionnaire.